Analysis on community involvement level in intangible cultural heritage: Malacca cultural community - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2014)
Intangible Cultural Heritage refers to human skills, practices, expression and instruments which form the transmitted practices of local cultures. The paper provides bivariate statistical analyses on the relationship between level of community involvement in Intangible Cultural Heritage and 10 demographic and socio-economic factors of Malacca community. The factors include gender, ethnicity, origin, age, marital status, religion, geographical location, education, household income and occupation. There exist community issues associate to the demographic and socioeconomic factors which contributed to deterioration in practices of local cultures. This paper discussed the community issues facing Malacca community in safeguarding their Intangible Cultural Heritage.